High Species Richness and Extremely Low Abundance of Cumacean Communities Along the Shelf and Slope of the Gulf of Guinea (West Africa) - Stȩpień, Anna; Pabis, Krzysztof; Sobczyk, Robert; Serigstad, Bjorn (Frontiers in Marine Science, 2021)
The Gulf of Guinea belongs to the most scarcely sampled marine basins in the oceans of the world. We have analyzed diversity and distribution patterns of cumacean communities on the shelf and slope, along the coast of Ghana. The material was collected in October and November of 2012 using a van Veen grab (0.1 m2) on nine transects. Six stations were located at each transect (25, 50, 100, 250, 500, and 1,000 m). Sixty-three species of Cumacea were recorded with Leucon and Eocuma as the most speciose genera, with 12 and eight species, respectively. Comparisons of species richness with literature data pointed that the Ghanaian coast hosts very diverse communities. About 95% of species were new to science, and the number of cumacean species known from the West Africa increased by over 100%. Nevertheless, most of the species had extremely low abundance, 13 singletons and 15 doubletons were found. Mean density of cumaceans was estimated at only 1.5 ind./0.1 m2. Species accumulation curve did not reach the asymptotic level, suggesting undersampling, despite the fact that sampling effort was high (250 samples). The highest species richness was recorded in the inner shelf (25–50 m) and on the slope (1,000 m). Cluster analysis separated shallow water communities from deeper regions on the shelf and upper slope. The most unique species composition was found at 1,000 m. Principal component analysis showed the importance of oxygen, sediments, and human-related disturbance for distribution of cumacean communities. In the shallows, oxygen content and presence of gravel were the most important factors structuring communities. In the deeper bottom areas (250–1,000 m), cumacean fauna was affected by local pollution, mainly by higher concentration of barium, other heavy metals, and THC.